FARMERS PERCEPTIONS AND PREFERENCES IN CIAMIS AND BANTUL ON ISLAMIC MICROFINANCE INSTITUTIONS (BMT) - Suraya Suraya (Universitas Hayam Wuruk Perbanas, 2010)
This research is done due to the fate of Indonesian people who, in majority, work as farmers. This community has not yet shown an increase in having more prosperous standard of living. This is assumed to be due to the insufficient capital, difficulty of access to financing, inability to provide collateral, and the limited number of the bank reach. This study attempts to reveal the role of Islamic micro-finance institutions or BMT for providing opportunities for the farmers. Yet, this rural community is unfamiliar with this institution. Therefore, it is impor- tant to see their perceptions, preferences, and acceptance for adopting such financial institu- tion. It employs the theory of perception, preferences, and level of adoption/acceptance of new things. The data were collected by means of questionnaires and interview. The study was conducted in Ciamis and Bantul Regencies from August to December 2009. It indicates the farmers’ perception level in Ciamis Regency high (91%), high-level preferences (97%), thus they can adopt Syariah microfinance institutions with a high level of acceptance (92%). In general, it can be concluded that there is no difference in perceptions, preferences, and the adoption of this bank by the communities in the two regencies.